Pemikiran Ekonomi Ibn Khaldun : Relevansinya Dalam Ekonomi Modern - Astri Hanum Lubis; Ahmad Zein Wahyudi; Ananda Wahid Siregar; M Aditya Sundawa (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the relevance of Ibn Khaldun's economic thought in the modern context. Ibn Khaldun emphasized the importance of wealth redistribution, economic cycles, and the role of the state in achieving economic stability and justice. The analysis reveals that zakat, infak, and sedekah significantly reduce social inequality and enhance societal welfare. Furthermore, Ibn Khaldun's theory of economic cycles highlights the necessity of good governance and productivity as the main pillars of economic growth. In the modern context, his perspectives are relevant for designing more inclusive and sustainable policies. By integrating these principles, Islamic economics can provide solutions to global challenges such as income inequality and economic instability.